Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1186/1472-6750-4-6
|View full text |Cite
|
Sign up to set email alerts
|

A large semi-synthetic single-chain Fv phage display library based on chicken immunoglobulin genes

Abstract: Background: Antibody fragments selected from large combinatorial libraries have numerous applications in diagnosis and therapy. Most existing antibody repertoires are derived from human immunoglobulin genes. Genes from other species can, however, also be used. Because of the way in which gene conversion introduces diversity, the naïve antibody repertoire of the chicken can easily be accessed using only two sets of primers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 45 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…A chicken recombinant antibody library which had been constructed earlier expressly to provide reagents for use in developing immunotests [11] was screened by panning against HSP65, a potentially important diagnostic antigen of both M. bovis and Mycobacterium tuberculosis [5]. Sequencing of a limited number of random clones showed that at least three different scFvs which recognised the target antigen had been obtained.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A chicken recombinant antibody library which had been constructed earlier expressly to provide reagents for use in developing immunotests [11] was screened by panning against HSP65, a potentially important diagnostic antigen of both M. bovis and Mycobacterium tuberculosis [5]. Sequencing of a limited number of random clones showed that at least three different scFvs which recognised the target antigen had been obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Single-chain Fvs were selected by panning a phage displayed repertoire derived from the immunoglobulin genes of the chicken (Nkuku Ò library) using methods described previously [11]. Phages displaying antibody fragments that bound to HSP65 were released at high pH and used to reinfect exponentially growing TG1 host cells.…”
Section: Single-chain Fvs From the Nkuku ò Librarymentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we describe two phage-displayed scFvs that are suitable for the serotype- and serogroup-specific detection of AHSV in double antibody sandwich (DAS)-ELISAs. Lca12, a serotype-specific scFv with a detection limit of 2 ng purified AHSV-3 per well, was selected with directly immobilized, sucrose gradient-purified AHSV-3 [8] as previously described in detail [17]. The serogroup-specific scFv G7 was isolated with trapped AHSV-8.…”
mentioning
confidence: 99%